JAMINAN SOSIAL DALAM TRANSISI - Faturochman Faturochman (Populasi, 1996)
As a poor reliever, social security has been effective in nature but economically in efficient. In developed countries, however, it has tended to be more efficient in the recent years. While the formal social security provided by the state is very limited, the informal social security in Indonesia has been cut back as indicated by the intervention of the authorities, commodification and monetization. The changing of the social security in developed countries as well as in Indonesia has really annotedthe vulnerable people.